HOAX AS A CRIMINAL ACT THROUGH ELECTRONIC MEDIA HOW TO OVERCOME HOAXES IN SOCIETY WITH A LEGAL SOCIOLOGY APPROACH - Rizky Amalia Saragih (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Hoax is a false notification in an attempt to deceive or influence readers or distributors to believe something, even though the news source used is fake and not circulating at all. This criminal act of hoax is regulated in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning ITE, where the criminal sanctions are contained in Article 45 A paragraph 1 and/or paragraph 2. A legal sociology approach is also needed in dealing with this act. This hoax crime uses various legal sociological theories, one of which, for example, uses the theory of legal effectiveness which is considered to be able to minimize this crime.